Para uma história da didática do ensino de línguas pela perspectiva de Historiografia Linguística - Batista, Ronaldo de Oliveira; Bastos, Neusa Barbosa (Linguarum Arena, 2019)
This article proposes a meta-historiographic reflection on modes of investigation of the history of didactics of language teaching in the research field of Historiography of Linguistics. This discussion is accompanied by brief case studies that aim to illustrate theoretical-methodological considerations presented. Our main aim is to show how processes that surround pedagogical practices, at different times throughout history, can be legitimate objects of a historiography that is concerned with understanding the construction and diffusion of knowledge about language.